Chromatin modifiers: regulators of cellular differentiation - Chen, Taiping (2013)
Cellular differentiation, by definition, is epigenetic. Genome-wide profiling of pluripotent cells and differentiated cells suggests global chromatin remodeling during differentiation, resulting in progressive transition from a relatively open chromatin configuration to a more compact state. Genetic studies in mouse models demonstrate major roles for a variety of histone modifiers and chromatin remodelers in key developmental transitions, such as the segregation of embryonic and extraembryonic lineages in blastocyst stage embryos, the formation of the three germ layers during gastrulation, and differentiation of adult stem cells. Furthermore, rather than merely stabilizing the gene expression changes driven by developmental transcription factors, evidence is emerging that chromatin regulators have multifaceted roles in cell fate decisions.